Insight on the Feasibility of Producing Durable Paper from Spruce Pulp using the Sulfate Process - Alireza Khakifirooz (BioResources, 2015)
Bleached spruce sulfate pulp was used in this study to produce paper handsheets. Ethylene diamine tetra acetic acid (EDTA( was introduced as a chelating agent in concentrations of 0, 0.25, 0.5, and 0.75%. The handsheets were exposed to UV light at wavelengths ranging from 330 to 440 nm, with time intervals of 0, 10, 20, 30, 40, and 50 h. Finally, the strength properties were measured based on ISO standards. The strength indices of the handsheets were improved by adding the proper concentration of EDTA chelating agent, in comparison with the control sample. Furthermore, increasing the aging time reduced the breaking length, tear strength, folding endurance, burst strength, and tensile strength. Tear index, tensile strength, tearing strength, bursting strength, and folding endurance were decreased respectively by 41.9, 3.1, 28.2, 29.7, and 8.6 percent without EDTA treatment by increasing the aging time.